2017
DOI: 10.1021/acs.cgd.7b00504
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Novel Lanthanide Metal–Organic Frameworks for Highly Efficient Visible-Light-Driven Dye Degradation

Abstract: Series of lanthanide metal−organic frameworks (Ln-MOFs) have been solvothermally synthesized using an anthracene-derived dicarboxylate ligand. The synthesized Ln-MOFs (Ce, Tb, Dy) show characteristics of broad-band visible-light absorption and efficient photoinduced charge generation. For the first time, Ln-MOFs have been employed as visible-light photocatalysts for rhodamine B (RhB) degradation in the presence of oxidant of hydrogen peroxide (H 2 O 2 ). Results show that these Ln-MOFs are highly efficient for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(34 citation statements)
references
References 43 publications
(72 reference statements)
1
33
0
Order By: Relevance
“…Lanthanide metal ions with high versatile coordination modes are widely adopted for the fabrication of MOFs. Xia and co-workers in 2017 reported that Ln-MOFs was synthesized from an anthracene-coordinated organic linker with Ce, Tb and Dy metal ion exhibit highly rhodamine B (RhB) degradation under visible light irradiation in the presence of H2O2 [8]. Other MOFs such as lanthanum-based metalorganic frameworks (La-MOFs) linked by aromatic dicarboxylic acid ligand [9] and lanthanide-based metal-organic frameworks (Ln-MOFs) with chalcone dicarboxylic acid ligand [10] also has been reported for the degradation of RhB.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide metal ions with high versatile coordination modes are widely adopted for the fabrication of MOFs. Xia and co-workers in 2017 reported that Ln-MOFs was synthesized from an anthracene-coordinated organic linker with Ce, Tb and Dy metal ion exhibit highly rhodamine B (RhB) degradation under visible light irradiation in the presence of H2O2 [8]. Other MOFs such as lanthanum-based metalorganic frameworks (La-MOFs) linked by aromatic dicarboxylic acid ligand [9] and lanthanide-based metal-organic frameworks (Ln-MOFs) with chalcone dicarboxylic acid ligand [10] also has been reported for the degradation of RhB.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5,6 ] By optimizing the chromophoric backbone of the organic ligands or adopting cheap metal sources, lots of earth‐abundant Cu I/II ‐, Co II ‐, Ni II ‐, Cd II ‐, and Hg II ‐based CPs with well‐tunable structural abundance and energy band structures have been rationally designed and successfully fabricated, [ 7–11 ] which have improved greatly the hydrogen evolution rate up to 26.1 mmol · g –1 · h –1 and degradation percentage of organic dyes up to 99 % in a very short time. [ 12 ] These enhanced activity benefits essentially from their well‐tailorable semiconductive nature, favorable microporous structures, and strengthened light‐harvesting ability. For example, irradiated by the sunlight in an open atmosphere, a 2‐mercaptonicotinate‐based double‐layered complex with highly stable Ni II 9 cluster shows slightly higher hydrogen production activity than some noble‐metal based photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of coordination polymers (CPs) continues to attract much interest not only because of their regular and interesting structural topologies, but also due to their potential applications, which make them useful as functional materials in various fields, such as molecular sensing, catalysis and magnetism (Zhao et al, 2017;Xia et al, 2017;Batrice et al, 2017;Yan et al, 2016;Bhattacharya et al, 2016). The deliberate selection of organic ligands containing appropriate coordination groups plays a crucial role in the formation of desirable structures (Marshall et al, 2015).…”
Section: Introductionmentioning
confidence: 99%